Overview of Filariasis - Mustika, I Made (Jurnal KESANS : Kesehatan dan Sains, 2025)
Lymphatic filariasis (LF) is a communicable tropical disease caused by filarial worms and transmitted through mosquito bites. The disease can lead to lymphedema, hydrocele, and permanent disability. This article presents an overview of the epidemiology, pathogenesis, diagnosis, management, and prevention of LF. The global program GPELF has contributed to a decline in cases through mass drug administration (MDA) and morbidity management. In Indonesia, the prevalence remains high, particularly in eastern regions. Early detection and comprehensive management are essential to support the sustainable elimination of filariasis.